A Simple Method for Estimation of Silicon Film Thickness in T-Gate Junction less Transistors - Jeon, Dae-Young; Park, So Jeong; Mouis, Mireille; Barraud, Sylvain; Kim, Gyu-Tae; Ghibaudo, Gerard (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2018)
Junction less transistors (JLTs) without PN-junctions near the source/drain are promising candidates for further development of CMOS technology. The Si thickness of tri-gate JLTs is crucial to understand their unique electrical properties related to bulk neutral and surface accumulation conduction. A simple method based on a unique operation mechanism is suggested for extraction of t(si) from measurements on tri-gate JLTs. The method was successfully applied to fabricated tri-gate JLTs and the extracted t(si) values were comparable with those of transmission electron microscopy. Furthermore, the validity of the method was confirmed by 2-D numerical simulation.
Keywords: NANOWIRE TRANSISTORS; CHANNEL WIDTH